A FORENSIC ANALYSIS OF ANDROID MALWARE - Abdumuminov Abdurafiq Abdurashidovich; Ibragimov Jalaliddin Obidjon o'g'li; Shoraimov Khusanboy Uktamboyevich (Journals Park Publishing, 2022)
We consider in this paper the analysis of a large set of malware and benign applications from the Android ecosystem. Although a large body of research work has dealt with Android malware over the last years, none has addressed it from a forensic point of view.
Keywords: Android Security, Digital Forensics, Malware Analysis, Malware development